Canna edulis KERR. and spirulina platensis as a prebiotic - Noriko, Nita; Tiara Perdana, Analekta; Wiramandiri, Fadly (International Journal of Engineering and Technology, 2018)
Probiotics have benefit on reducing the number of pathogenic bacteria in human the digestive system. One way to keep the amount of probiotics in the human body is to consume prebiotics. One source of prebiotic food is red C. edulis Kerr because contain starch and fiber. S. platensis is a microalgae having 60-70% protein contain and when combined with flour from red tubers C.edulis Kerr will increase nutritional contain. The research about the potency of red tubers Kerr flour and S. platensis powder as prebiotics has done by growing L. casei rhamnosus in De Mann Rogosa and Sharpe Agar (MRSA) as control and control negative without glucose and several modified MRSA. There were glucose MRSA substituted to C.edulis Kerr (MRSA C), peptone to S. platesis (MRSA P) , glucose and peptone to C.edulis Kerr flour and S. platensis (MRSA CP), and also complete flour composite C. edulis, S. platensis and Acalypha indica powder as additive oresevative substantive (MRSA CPA). Indicator potencial flour of Kerr, S. platensis powder in modified medium as prebiotics by calculating Total Plate Count (TPC) methode and test for anti-pathogen bacteria. Gram Test was conducted to make sure the kind of bacteria. The results showed L. casei rhamnosus grew in MRSA and modified medium. The total population of L. casei rhamnosus in MRSA, MRSA C, MRSA CP and MRSA CPA are not significantly (P< 0,05). MRSA P is the highest total of L. casei rhamnosus and when growing in modified MRSA CP can inhibit the growth of E. coli. Gram test bacteria in clear zone showed positif. It indicate L. casei rhamnosus. C. edulis Kerr and S.platensis in modified MRSA have potential as prebiotics by invitro methodology. A. indica in MRSA CPA did not inhibit growth of L. casei rhamnosus.Â Â